Revenge and gender in classical, medieval, and Renaissance literature - Dawson, Lesel; McHardy, Fiona (Edinburgh University Press, 2018)
Title Page -- Copyright -- Contents -- List of Figures -- Acknowledgements and Dedication -- Introduction: Female Fury and the Masculine Spirit of Vengeance -- PART I THE GENDERING OF REVENGE -- 1 Why are the Erinyes Female? or, What is so Feminine about Revenge? -- 2 Re-marking Revenge in Early Modern Drama -- PART II F RIENDS AND FAMILY - 'REVENGING HOME' -- 3 Vengeance and Male Devotion in Laxdæla saga and Njáls saga -- 4 'Now I am Medea': Gender, Identity and the Birth of Revenge in Seneca's Medea -- 5 The Avenging Daughter in King Lear -- 6 'Brother Unkind': Annabella's Heart in 'Tis Pity She's a Whore -- PART III WOMEN'S WEAPONS -- 7 Cursing-Prayers and Female Vengeance in the Ancient Greek World -- 8 'The Power of Our Mouths': Gossip as a Female Mode of Revenge -- 9 'Women's Weapons': Education and Female Revenge on the Early Modern Stage -- PART IV WOMEN TRANSMOGRIFIED -- 10 The Vengeful Lioness in Greek Tragedy: A Posthumanist Perspective -- 11 'She's Turned Fury': Women Transmogrified in Revenge Plays -- PART V LAMENTATION, GENDER ROLES AND VENGEANCE -- 12 A Phrygian Tale of Love and Revenge: Oenone Paridi (Ovid Heroides 5) -- 13 Lament and Vengeance in the Alliterative Morte Arthure -- 14 What's Hecuba to Shakespeare? -- 15 'Nursed in Blood': Masculinity and Grief in Marston's Antonio's Revenge -- 16 Outfacing Vengeance: Heroic Dying in Webster's The Duchess of Malfi and Ford's The Broken Heart -- List of Contributors -- Index